NUMERICAL TESTS OF VANISHING DIFFUSION STABILIZATION IN OLDROYD-B FLUID FLOW SIMULATIONS - Pires, Marília (2021)
This work presents some numerical tests of finite element solution of incompressible Oldroyd-B fluids flows, using different types of numerical stabilization. In this study the diffusive term (Laplacian of extra stress) is added to the tensorial constitutive relation where it is multiplied by a coefficient, that is variable in time. The goal is to make this diffusion coefficient vanish in time, so that the final solution remains unaffected by the added diffusion term. A series of numerical tests was performed for the steady two-dimensional Oldroyd-B fluid flow in corrugated channel (tube) to compare different versions of the vanishing stabilization terms and assess their efficiency in enforcing the solution convergence, without affecting the final steady state.